Memories in Translation: A Life between the Lines of Arabic Literature by Denys Johnson-Davies (Cairo and New York: The American University in Cairo Press, 2006. 139 pages.) (American Journal of Islam and Society, 2007)
The book’s title and subtitle are both concise and apt characterizations. Aftermore than sixty years of work as a translator and a writer, Johnson-Daviestakes the reader on a journey through memories told as if relived throughwriting. The language is clear, fluent, and businesslike. Interspersed in theaccount are humorous anecdotes about some of his more embarrassing experiencesas a translator.The book has a foreword by Naguib Mahfouz (d. 2006), the Nobel Prizewinning(1988) Egyptian writer with whom the author had an acquaintanceshipgoing back sixty years and several of whose books he translated.Twenty-two photographs show the author at various times in his life (1922-2000) at work, with friends, writers, poets, and various personalities. Everyphotograph is fully documented as regards location, names, date, and other ...